Supportive Postpartum Care Reduces Postpartum Anxiety in Mothers with Twins: A Pilot Study - Lina Ayu Marcelina; Imami Nur Rachmawati; Wiwit Kurniawati (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
Postpartum mothers with twins are more prone to mental health problems, particularly anxiety. However, research regarding the appropriate interventions to overcome anxiety in postpartum mothers with twins is limited. Anxiety has an impact on the health of both mother and baby. We conducted a pilot study to minimize the risks to mothers and babies, which was supportive postpartum care (SPC). The study was performed to five postpartum mothers with twins during hospitalization. SPC was employed by providing physical support, which was in the form of breast care and oxytocin massage, psychological support in the form of relaxation techniques, information support in the form of education, and advocacy support in the form of husband involvement. This method was effective for postpartum mothers with twins in reducing anxiety, increasing breastfeeding effectiveness, increasing knowledge, and improving the husband’s involvement in care. This study showed that SPC can reduce postpartum anxiety among postpartum mothers with twins effectively. A very good increase of LATCH score and knowledge were reported in 3 out of 5 mothers. Families, especially husbands, were advised to continue providing care support through the role division at home.